ANALISIS KASUS WANPRESTASI PADA PT. ASURANSI JIWASRAYA - Fara Aprodita N; Zhafirah Salsabila; Imelda Vratista; Tiara Rebecca K.S; Anastasya Regina S.C; Dwi Aryanti Ramadhani (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Qualifying insurance as part of contract law does not rule out the possibility of default between the insurance company and the policy holder. This company has been established since 1859 and is the oldest financial services company in Indonesia. Being the only and oldest insurance company owned by the Indonesian Government does not make it an agency that is always loyal and has integrity. This is proven by the existence of a default case that occurred between PT. Jiwasraya with policy holders. This study was conducted to understand the root causes of the a quo case, starting from the chronology, the impact on policy holders, and what legal protection options policy holders can take. Through an analytical approach, this research tries to explain that legal action through lawsuits and reports in criminal and civil cases can be carried out to seek accountability for the loss of material rights of policy holders.